2022
DOI: 10.3389/fimmu.2022.807343
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Differential Responsiveness to Clostridium perfringens and Lactococcus lactis by Avian Small Intestine Macrophages and T Cells

Abstract: Tissue resident immune system cells in the chicken intestine play a significant role in the protection against pathogens. However, very little is known about these cells. The current study was conducted to further characterize chicken intestinal immune system cells. Furthermore, this study aimed to assess the immune modulatory action of a highly virulent Clostridium perfringens, a commonly found chicken intestinal microbe, in comparison with a non-commensal, Lactococcus lactis, on intestine-derived immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Previous work, albeit using in vitro and ex vivo experiments, has shown that virulent CP can activate chicken macrophages, resulting in an increased frequency of these cells (22, 38, 39). Another study also found that an ex vivo stimulation of chicken intestine–derived lymphocytes with a virulent CP strain (CP4) led to an activation of γδ T-cells, as determined by an upregulated surface expression of CD25 and intracellular IFNγ production in these cells (21). To this end, in the present study, the frequency of γδ T-cells in the CT of CP26-infected chickens was also found increased, suggesting involvement in the host response during NE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work, albeit using in vitro and ex vivo experiments, has shown that virulent CP can activate chicken macrophages, resulting in an increased frequency of these cells (22, 38, 39). Another study also found that an ex vivo stimulation of chicken intestine–derived lymphocytes with a virulent CP strain (CP4) led to an activation of γδ T-cells, as determined by an upregulated surface expression of CD25 and intracellular IFNγ production in these cells (21). To this end, in the present study, the frequency of γδ T-cells in the CT of CP26-infected chickens was also found increased, suggesting involvement in the host response during NE.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that protection against NE is associated with secretory products from virulent, but not avirulent, CP (14) and identified certain secreted proteins as potential vaccine candidates (7,15,16). Studies aimed at characterizing CP-induced immune responses have shown elevated intestinal gene expression of antimicrobial peptides and cytokines such as interleukin (IL)-1b, IL-6, IL-8, IL-10, IL-12, and transforming growth factor b in NEaffected chickens (17,18,19). Our recent studies also found that broiler chickens experimentally infected with virulent CP had increased expression of proinflammatory cytokine genes IL-1b, IL-6, or interferon (IFN)c, in the intestinal and cecal tonsil (CT) tissues (13,20).…”
Section: Incidences Of Necrotic Enteritis (Ne) In Chickens Caused Bymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, broiler chickens coinfected with E. maxima and virulent C. perfringens induced an increased intestinal gene expression of pro-inflammatory cytokines (IL-1β, IFNγ, IL-17, IL-8, and others) [ 16 , 36 ], while in vitro stimulation of chicken intestinal epithelial cells with virulent C. perfringens or purified alpha-toxin led to an increased transcription of IL-6, IL-8, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF), and nuclear factor kappa-B (NFkB) genes [ 37 ]. In support of these findings, macrophages have been shown as the likely source of such mucosal inflammatory responses [ 18 , 38 ] [Kulkarni, et. al., 2023; unpublished].…”
Section: Discussionmentioning
confidence: 81%